Kajian Stilistika dalam Lagu Happy Asmara Wis Tatas - Natalia, Kristin (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2023)
The lyrics of this song are the lyrics of a dangdut song performed by Happy Asmara in Javanese. The interesting thing to study further is the use of diction and the theme using stylistics, namely looking at the style of language used. Stylistic studies are directed to discuss the content of literary works. In general, stylistic studies include diction or word choice (lexical choice), sentence structure, figure of speech, partnership, rhyme patterns, and dimensions used by the author or contained in literary works. This study aims to analyze the use of diction and themes contained in the lyrics of the Dangdut Happy Asmara song entitled